Mediating Role of Illness Representation Among Social Support, Therapeutic Alliance, Experience of Medication Side Effects, and Medication Adherence in Persons With Schizophrenia - Malatee Rungruangsiripan (2018)
The purpose of this cross-sectional research study was to examine factors affecting medication adherence in Thai individuals with schizophrenia. The Common-Sense Model of Illness Representation was used to guide the study. Two hundred twenty-five subjects met the inclusion criteria and were interviewed. Variables of interest focused on experience of medication side effects, therapeutic alliance, social support, illness representation, and behavior change with medication adherence. Results indicated that therapeutic alliance and the experience of medication side effects enhanced illness representation, which in turn led to an intention to change adherence behavior. Social support did not alter illness representation or adherence behavior. Because illness representation positively influenced patients' intention to change adherence behavior, mental health nurses should promote patients' perception about their illness to enhance medication adherence. © 2011 Elsevier Inc.